The entrepreneurial teacher behavior scale: a scale adaptation study gi̇ri̇şimci̇ öğretmen davranışları ölçeği: Bi̇r ölçek uyarlama çalışması - ÇETİN, MÜNEVVER (My University, 2022)
© 2022. Milli Egitim. All Rights Reserved.The purpose of this study is to conduct translation, linguistic equivalence, validity, reliability and item analysis studies for the adaptation of the scale developed by Van Dam, Schipper and Runhaar (2010) for teachers’ entrepreneurial behaviors into Turkish. The working group of the research consists of 422 teachers working in public schools on the Anatolian side of Istanbul in the academic year 2020-2021. The Turkish form of the scale was created using forward (English-Turkish) and backward (Turkish-English) translation methods in line with the opinions of field experts. In order to test the language equivalence of the scale, Turkish and original English forms were administered to 42 English teachers at three-week intervals, and positive and significant relationships were found between the scores obtained from both scales. Explanatory and confirmatory factor analysis was carried out within the scope of validity study and it was determined that the scale has a 3-dimensional structure that explains %61.986 of the total variance. Within the scope of the reliability study, the Cronbach Alpha (α) reliability coefficient of the general and sub-dimensions of the scale was.719 and.863; McDonald Omega (ω) coefficient was calculated to have values between.723 and.869 and Combined Reliability (cR) coefficient between.824 and.891. Item-Test Correlation and Sub-Upper Group Analysis were used to determine the item analysis. As a result of these analyzes, it was concluded that each item of the scale is distinctive.

Öz: Bu araştırmanın amacı Van Dam, Schipper ve Runhaar (2010) tarafından öğretmenlerin girişimci davranışlarına yönelik geliştirilen ölçeğin Türkçe’ ye uyarlamasına yönelik çeviri, dilsel eşdeğerlik, geçerlik, güvenirlik ve madde analizi çalışmalarını yapmaktır. Araştırmanın çalışma grubunu, 2020 – 2021 eğitim ve öğretim yılında İstanbul ilinin Anadolu Yakasındaki devlet okullarında görev yapan 422 öğretmen oluşturmaktadır. Ölçeğin Türkçe formu alan uzmanlarının görüşleri doğrultusunda ileri (İngilizce-Türkçe) ve geri (Türkçe-İngilizce) çeviri yöntemleri kullanılarak oluşturulmuştur. Ölçeğin dil eşdeğerliliğini test etmek amacıyla Türkçe ve orijinal İngilizce formu üç hafta arayla 42 İngilizce öğretmenine uygulanmış ve her iki ölçekten elde edilen puanlar arasında pozitif ve anlamlı ilişki saptanmıştır. Geçerlik çalışması kapsamında açımlayıcı ve doğrulayıcı faktör analizi gerçekleştirilmiş ve ölçeğin toplam varyansın %61.986’sını açıklayan 3 boyutlu bir yapıya sahip olduğu tespit edilmiştir. Güvenirlik çalışması kapsamında ölçeğin geneli ve alt boyutlarının Cronbach Alfa (α) güvenirlik katsayısı .719 ile .863; McDonald Omega (ω) katsayısı.723 ile .869 ve Birleşik Güvenirlik (cR) katsayısı .824 ile .891 arasında değerler aldığı hesaplanmıştır. Madde analizinin belirlenmesinde Madde-Test Korelasyonu ve Alt-Üst Grup Analizi kullanılmıştır. Bu analizlerin neticesinde ölçeğin her bir maddesinin ayırt edici olduğu sonucuna ulaşılmıştır
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Eğitim; Social Sciences and Humanities; Sociology; Education; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; Confirmatory factor analysis; Entrepreneurial behavior; Entrepreneurship; Exploratory factor analysis; Reliability; Teacher; Validity; Girişimcilik; girişimci davranış; öğretmen; açımlayıcı faktör analizi; doğrulayıcı faktör analizi; geçerlik; güvenirlik